Not “Much Room” in the Heart: A Rare Case of a Massive Intracardiac Candida Mass - Ali Haider Jafry; Sardar Hassan Ijaz; Murtaza Mazhar; Areeba Shahnawaz; Ali Yousif (Case Reports in Infectious Diseases)
Introduction. Coupled with the increasing use of indwelling vascular catheters and prosthetic cardiac valves is an uptrend in sepsis secondary to fungemia. An insidious onset often shrouds the initial diagnosis, contributing to poor outcomes. Candida infective endocarditis (CIE) is a feared complication of candidemia, associated with high mortality rates. It requires prolonged hospital stays for medical and, often, surgical management. We report a case of a massive intracardiac Candida mass in an adult with native valve CIE. Case. A 51-year-old male on chronic total parenteral nutrition (TPN) because of bowel resection presented with fevers, night sweats, and unintentional weight loss. He was febrile and tachycardiac on admission, with a benign physical examination. Laboratory workup showed elevated inflammatory markers and an acute kidney injury. Extended blood cultures showed growth of Candida glabrata (C. glabrata) and Candida dubliniensis (C. dubliniensis). Transthoracic (TTE) and transesophageal echocardiography revealed a large mobile right atrial mass (4 cm × 6 cm × 2.5 cm), extending to the right ventricular outflow tract. Since he was a poor surgical candidate, management with micafungin was initiated and continued for 8 weeks. He responded well to the regimen with resolution of the fungal mass on follow-up TTE 3 months later. In anticipation of the future need for TPN, he continues on lifelong suppressive oral fluconazole. Conclusion. CIE may be an insidious complication of indwelling central venous catheters, necessitating a high index of suspicion. Conservative management, with antifungal therapy, can yield favorable outcomes in poor surgical candidates.